Measuring the effects of COVID-19-related disruption on dengue transmission in southeast Asia and Latin America: a statistical modelling study - Chen, Yuyang; Li, Naizhe; Lourenço, José; Wang, Lin; Cazelles, Bernard; Dong, Lu; Li, Bingying; Liu, Yang; Jit, Mark; Bosse, Nikos I; Abbott, Sam; Velayudhan, Raman; et al. (The lancet. Infectious diseases, 2022)
The COVID-19 pandemic has resulted in unprecedented disruption to society, which indirectly affects infectious disease dynamics. We aimed to assess the effects of COVID-19-related disruption on dengue, a major expanding acute public health threat, in southeast Asia and Latin America.
Online verfügbar 2. März 2022, Artikelversion 20. April 2022
Gesehen am 21.02.2023